2012
DOI: 10.3390/v4113069
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Dynamics of Viruses are Differentially Affected by Parasitoids Depending on the Mode of Transmission

Abstract: Relationships between agents in multitrophic systems are complex and very specific. Insect-transmitted plant viruses are completely dependent on the behaviour and distribution patterns of their vectors. The presence of natural enemies may directly affect aphid behaviour and spread of plant viruses, as the escape response of aphids might cause a potential risk for virus dispersal. The spatio-temporal dynamics of Cucumber mosaic virus (CMV) and Cucurbit aphid-borne yellows virus (CABYV), transmitted by Aphis gos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…; Dáder et al . ). Natural enemies may even be indirectly responsible for a significant proportion of new infections, though they also reduce the overall number of vectors through consumption (Hodge, Hardie & Powell ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Dáder et al . ). Natural enemies may even be indirectly responsible for a significant proportion of new infections, though they also reduce the overall number of vectors through consumption (Hodge, Hardie & Powell ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, natural enemies of aphids – the primary vectors of many plant viruses – can potentially influence virus transmission to new hosts through impacts on aphid behaviour and dispersal (Chau & Mackauer ; Dáder et al . ). Several studies have reported increased rates of virus transmission by vectors when predators or parasitoids were introduced into mesocosms containing infected and susceptible host plants and aphids (Christiansen‐Weniger, Powell & Hardie ; Smyrnioudis et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Vectors forage in heterogenous environments and interact with other herbivores and predators as they move within and among host plants. Interactions between vectors and predators, hosts, and other herbivores can in turn affect the transmission of plant viruses by altering vector abundance (density-mediated effects) and behavior (trait-mediated effects; Power 1991, Smyrnioudis et al 2001, Malmstrom et al 2005, Hodge and Powell 2008, Thaler et al 2010, D ader et al 2012, Finke 2012, Ostfeld and Keesing 2012, Long and Finke 2015, Chisholm et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Natural enemies of insect vectors also play an important role in altering virus spread patterns by using different strategic methods. According to Dáder et al (2012) Aphid parasitoid, Aphidius colemani Viereck 1912 increased the spread of nonpersistently transmitted CMV in cucumber, but reduced the spread of persistently transmitted Cucurbit aphid-borne yellows virus.…”
Section: Insect Vector Ecologymentioning
confidence: 99%